RETRACTED: Analytical study on longitudinal crack control for B70 mono-block pre-stressed concrete sleepers. (March 2015) - Hasheminezhad, Araz
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of the Editor-in-Chief. The author has published under his own name research work taken from the MSc Thesis by Mahdi Bayat Avarzamani entitled "Numerical analysis of pre-tensioned concrete sleepers affected by additional stresses from rail clamp system". The thesis was submitted to the Graduate Studies Office of the Department of Civil Engineering, Malayer Branch, Islamic Azad University. The thesis was supervised by Dr. Freydoon Rezaei. A close examination of the thesis and paper revealed strong evidence that the primary data published in the paper could only have come from the thesis and the author had made no acknowledgement of the work of Mr. Avarzanani or Dr. Rezaei. One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.